PHYTOCHEMICAL, GAS CHROMATOGRAPHY WITH MASS SPECTROMETRY ANALYSIS OF ANDROGRAPHIS SERPYLLIFOLIA METHANOL LEAF EXTRACT AND ITS ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES - R, MADHANKUMAR; S, MURUGESAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study is to evaluate the preliminary study of phytochemical screening and biological applications of Andrographis serpyllifolia methanol leaf extracts. Methods: The methanol leaf extracts of A. serpyllifolia was prepared using Soxhlet apparatus and the extract was analyzed using gas chromatography with mass spectrometry (GC-MS). In vitro antioxidant activity was determined by superoxide dismutase, catalase, glutathione peroxidase, and glutathione S-transferase. Further, the antibacterial activity of methanolic leaf extract of A. serpyllifolia was tested against various human pathogens by using agar disc diffusion method. Results: Preliminary phytochemical screening and GC-MS results revealed phenols, aromatic carboxylic acids, and esters in the chloroform extract to be the molecules responsible for the antioxidant and antibacterial activity of A. serpyllifolia methanol extract and fractions showed the presence of various secondary metabolites present. Conclusion: The present study strongly recommended that the methanolic extract of A. serpyllifolia leaves possesses compounds that inhibit the growth of microbes as wells excellent antioxidant activities. The study further suggested the potential therapeutic use of these extract in cancer study.